Principle of object support by Rope deformation and its application to Rope climbing by snake robot. (3rd May 2023) - Watanabe, Ryota; Tanaka, Motoyasu
Abstract : This study proposes a principle of object support by rope deformation and demonstrates the application of this principle to the operation of a snake robot that moves up and down on a rope. To realize the object support, the minimum tension required to support the object under deformation of the rope and the principle and effect of rotation of the object's posture are considered. An effective method for winding the rope is additionally examined. For the rope-climbing motion of the snake robot, we designed and fabricated a snake-shaped robot that can apply the principle of object support by rope deformation using multiple joints. GRAPHICAL ABSTRACT: UF0001